The Challenge and Relevance of The Vow of Obedience Today: Reflection on Spirituality Based on Constitution of the osf Reute Sibolga Congregation - Tumanggor, Rosidawati Ros; Suhardi, Arnold; Daeli, Onesius Otenieli (Litbang STFT Widya Sasana Malang, 2025)
Vows are promises that religious individuals make to remain faithful to God, including the evangelical counsels of obedience, chastity, and poverty. These vows are fundamental to spiritual life and must be actively lived. The vow of obedience is meant to help individuals faithfully follow God's will freely and responsibly, expressed through mission work, communal living, and service to the Church. However, living out this vow today is challenging due to societal changes and the fast-paced, individualistic nature of modern life. Thus, the vow of obedience needs to be revisited to ensure it stays true to the principles in the OSF constitution and is not diminished by changing times. It also represents a commitment to social responsibility in the context of globalization and technological advancement. This article uses qualitative research through literature study to examine the challenges and deeper understanding of the vow of obedience in the OSF congregation. In conclusion, the vow of obedience remains relevant today and is a source of strength for religious individuals in fulfilling their calling. Religious individuals today are called to be humble and ready to be sent.